Bureaucracy and democracy in the American century: A.F. Davies on administration and the `knowledgeable society' - Walter, James (1999)
American observation has shaped Australian social analysis for most of the 20th century. The high point in American influence on Australia was arguably between the 1940s and the 1980s. Its influence in Australian political science can be traced through the work of an insightful interpreter of the Australian polity and its bureaucratic practices, A.F. Davies (1924-87). The tensions between `knowledge criteria' and `political criteria', between bureaucracy as a `stain' and the best means of delivering equalising outcomes, between the necessary skills of `program professionals' and the demands of broad participation were at the core of his work. Testing his propositions 10 years after his final work shows Davies accurately foreshadowed the essentials of what he designated `the steady evaporation of politics' Davies's reflection on Australia was productively shaped by dialogue with America as the metropolitan culture. His insistence that the comparative framework, the bureaucratic imperative of complex organisation, and an interpretative sense of political cultures should inform political analysis remains an important message as we address the problems of the 1990s. - Reproduced
Keywords: Bureaucracy